Movinf towords happy lane - Tahir Nawaz (Islamabad : PN Book Club Publishers, 2018)
Discusses biological and psychological aspects of stress, techniques for stress reduction, and stress management programs.
0
Keywords: Stress management -- poetry; Stress (Psychology); Stress management